Association of dietary inflammatory index and specific nutrients with anti-seizure medications use among U.S. adults - Guoli Ma; Jiayu Zhang; Hexing Wang; Junlan Qiu; Xiaochen Shu (Medicine, 2026)
Anti-seizure medications (ASMs) are prescribed for epilepsy and other conditions including neuropathic pain and migraine. Dietary patterns may modulate inflammation, which has been implicated in neurological conditions. This study aimed to investigate the association of dietary inflammation, measured by the dietary inflammatory index (DII), and specific nutrients and ASM use among U.S. adults. Data were obtained from the National Health and Nutrition Examination Survey from 2013 to 2020 with 11,536 participants (46.44% female). A modified DII was calculated using 26 dietary parameters from a single 24-hour recall. ASM use was identified based on self-reported use within the past 30 days. Logistic regression models adjusted for sociodemographic and lifestyle factors were used to assess associations. Participants in the highest DII tertile (T3) had significantly higher ASM use compared to the intermediate tertile (T2) (OR = 1.63; 95% confidence interval: 1.15–2.34; P < .01). Restricted cubic spline analysis revealed a nonlinear, J-shaped relationship. The association was more prominent among females, unemployed and those with lower education, and with insufficient physical activity. Higher intake of fiber, vitamin A, and selenium was inversely associated with ASM use; however, positive associations for vitamins D, C, and B12 likely reflect supplementation practices. A pro-inflammatory diet was observed to be associated with higher ASM use, particularly in females and socioeconomically disadvantaged groups. Due to the cross-sectional design and possible potential reverse causality, these findings require confirmation in prospective studies.